Quality problem solving with PDCA cycle - Foulla, Boulesnane (Journal of Excellence for Economics and Management Research, 2021)
This study identified that is very essential to apply the PDCA cycle for solving problem quality in any organization, regardless its type or size. PDCA cycle and basic quality tools were used to analyze the quality problems and implement a successful solution. PDCA cycle is an iterative four steps managing technique, the Plan phase consisted of investigating the problem. The Do phase consisted of implementing the corrective actions and the effectiveness of the improvements were verified in the Check phase. The final phase of PDCA was Act where other opportunities for implementing the corrective actions would be sought. In every phase of PDCA cycle, we need to use the seven basic quality tools.